Answer:
I think it is in order
Step-by-step explanation:
not to sure though sorry
Answer:
Step-by-step explanation:
Quadratic equations of the form (x - h)^2 + k = 0 can be solved using square roots: Take the square root of both sides, prefacing the right side with " ± "
Answer is a hope it helps
Answer:
f(2) = -40
Step-by-step explanation:
Just substitute x=2 into the function:
f(x) = 2x³ - 3x² - 18x - 8
f(2) = 2(2)³ - 3(2)² - 18(2) - 8
f(2) = 2(8) - 3(4) - 36 - 8
f(2) = 16 - 12 - 44
f(2) = 4 - 44
f(2) = -40